2012
DOI: 10.1097/tin.0b013e31826f8da5
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring as the Segue to Leadership in Dietetics

Abstract: The purpose of this study was to determine the process/model of how dietitians develop into leaders, based on descriptions provided by the Academy of Nutrition and Dietetics (formerly the American Dietetic Association) leaders. The qualitative methodology of grounded theory included semistructured audio-recorded telephone interviews of 25 nationally elected or appointed leaders of the Academy in the United States. Open coding identified the themes: born/made, mentoring, horizontal development, personal growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated that mentoring has the potential to aid leadership development in healthcare38 and to develop the physiotherapy profession 39. In a study investigating the leadership paths of dietitian leaders, mentoring was found to be the segue to leadership in dietetics 40. Dietitian leaders recognised that the encouragement, nurturing and support of a mentor were essential factors in their leadership development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that mentoring has the potential to aid leadership development in healthcare38 and to develop the physiotherapy profession 39. In a study investigating the leadership paths of dietitian leaders, mentoring was found to be the segue to leadership in dietetics 40. Dietitian leaders recognised that the encouragement, nurturing and support of a mentor were essential factors in their leadership development.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most research regarding leadership within dietetics is focused on those in formal leadership roles [13][14][15][16][17] and students or dietetics education. 18,19 Gregoire and Arendt 20 discussed the ambiguity of what leadership means to the dietetics profession and recommended more research.…”
mentioning
confidence: 99%